2008
DOI: 10.1016/j.mri.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of the quantitative assessment of cartilage morphology and trabecular bone structure with magnetic resonance imaging at 7 T

Abstract: To assess the reproducibility of quantitative measurements of cartilage morphology and trabecular bone structure of the knee at 7 T, high-resolution sagittal spoiled gradient-echo images and highresolution axial fully refocused steady-state free-precession (SSFP) images from six healthy volunteers were acquired with a 7-T scanner. The subjects were repositioned between repeated scans to test the reproducibility of the measurements. The reproducibility of each measurement was evaluated using the coefficient(s) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…28 Another previous human study reported good repeatability for cartilage thickness measurements using a 7T scanner, with a coefficient of variation of 1.13%. 29 Good repeatability of MRI cartilage thickness measurements was also found in a study of asymptomatic human hip joints. 30 Inter-rater and intra-rater reliability of human cadaver femoral head cartilage thickness measurements from 3D-spoiled gradient echo pulse sequences have been found to be very high (<0.98) 31 and highresolution MRI cartilage thickness evaluation was also found to have good correlation with direct imaging analysis of surgically removed cartilage.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…28 Another previous human study reported good repeatability for cartilage thickness measurements using a 7T scanner, with a coefficient of variation of 1.13%. 29 Good repeatability of MRI cartilage thickness measurements was also found in a study of asymptomatic human hip joints. 30 Inter-rater and intra-rater reliability of human cadaver femoral head cartilage thickness measurements from 3D-spoiled gradient echo pulse sequences have been found to be very high (<0.98) 31 and highresolution MRI cartilage thickness evaluation was also found to have good correlation with direct imaging analysis of surgically removed cartilage.…”
Section: Introductionmentioning
confidence: 71%
“…This finding was similar to previously published findings. [29][30][31] One limitation of the current study was that no inter-observer comparisons were made. However, previous studies have found good inter-observer repeatability for MRI measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The OA process was simulated and supervised [18]. Rat models were selected due to their reasonable time life for observing the OA process from the beginning to the end [12]. High-resolution MRI technique was used due to its non-invasive characteristic [8] and especially its quality for analyzing small joint of animal models [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, morphological (volume, thickness, and curvature) properties and contact area were analyzed and quantified by using geometrical computing techniques. In literature, morphological assessment (volume and thickness) was largely studied [6,[8][9][10]12,25]. Contact area properties of the cartilage were also quantified [16,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation